Reduced Glutathione in Modulation of Salt Stress on Sour Passion Fruit Production and Quality - Weslley Bruno Belo de Souza; Geovani Soares de Lima; Lauriane Almeida dos Anjos Soares; Mirandy dos Santos Dias; Brencarla de Medeiros Lima; Larissa Fernanda Souza Santos; Valeska Karolini Nunes Oliveira; Rafaela Aparecida Frazão Torres; Hans Raj Gheyi; Lucyelly Dâmela Araújo Borborema; André Alisson Rodrigues da Silva; Vitor Manoel Bezerra da Silva; et al. (Plants)
This study evaluated the effects of reduced glutathione (GSH) application on the production and quality of sour passion fruit irrigated with brackish water in the semi-arid region of Paraíba, Brazil. The experiment was conducted in drainage lysimeters under greenhouse conditions at the Center of Technology and Natural Resources of the Federal University of Campina Grande (UFCG). Treatments combined five levels of electrical conductivity of brackish irrigation water (Bw: 0.4, 1.2, 2.0, 2.8, and 3.6 dS m−1) and four GSH concentrations (0, 40, 80, and 120 mg L−1), arranged in a randomized block design with three replicates. Salinity levels above 0.4 dS m−1 negatively affected fruit production and post-harvest quality of ‘BRS GA1’ sour passion fruit. Foliar application of 120 mg L−1 GSH increased fruit yield, while 74 mg L−1 GSH mitigated salt stress effects on production and pulp chemical quality. The ‘BRS GA1’ cultivar was highly sensitive to salinity, showing a 26.9% yield reduction per unit increase in Bw electrical conductivity above 0.4 dS m−1. The results suggest that GSH can alleviate salt stress damage, improving crop productivity and fruit quality under semi-arid conditions.